Physician's sociodemographic profile and distribution across public and private health care: an insight into physicians' dual practice in Brazil - Bruno Alonso Miotto; Aline Gil Alves Guilloux; Alex Jones Flores Cassenote; Giulia Marcelino Mainardi; Giuliano Russo; Mário César Scheffer (BMC, 2018)
Abstract Background The intertwined relation between public and private care in Brazil is reshaping the medical profession, possibly affecting the distribution and profile of the country's medical workforce. Physicians' simultaneous engagement in public and private services is a common and unregulated practice in Brazil, but the influence played by contextual factors and personal characteristics over dual practice engagement are still poorly understood. This study aimed at exploring the sociodemographic profile of Brazilian physicians to shed light on the links between their personal characteristics and their distribution across public and private services. Methods A nation-wide cross-sectional study using primary data was conducted in 2014. A representative sample size of 2400 physicians was calculated based  on the National Council of Medicine database registries; telephone interviews were conducted to explore physicians' sociodemographic characteristics and their engagement with public and private services. Results From the 2400 physicians included, 51.45% were currently working in both the public and private services, while 26.95% and 21.58% were working exclusively in the private and public sectors, respectively. Public sector physicians were found to be younger (PR 0.84 [0.68-0.89]; PR 0.47 [0.38-0.56]), less experienced (PR 0.78 [0.73-0.94]; PR 0.44 [0.36-0.53]) and predominantly female (PR 0.79 [0.71-0.88]; PR 0.68 [0.6-0.78]) when compared to dual and private practitioners; their income was substantially lower than those working exclusively for the private (PR 0.58 [0.48-0.69]) and mixed sectors (PR 0.31 [0.25-0.37]). Conversely, physicians from the private sector were found to be typically senior (PR 1.96 [1.58-2.43]), specialized (PR 1.29 [1.17-1.42]) and male (PR 1.35 [1.21-1.51]), often working less than 20 h per week (PR 2.04 [1.4-2.96]). Dual practitioners were mostly middle-aged (PR 1.3 [1.16-1.45]), male specialists with 10 to 30 years of medical practice (PR 1.23 [1.11-1.37]). Conclusion The study shows that more than half of Brazilian physicians currently engage with dual practice, while only one fifth dedicate exclusively to public services, highlighting also substantial differences in socio-demographic and work-related characteristics between public, private and dual-practitioners. These results are consistent with the international literature suggesting that physicians' sociodemographic characteristics can help predict dual practice forms and prevalence in a country.